Implementasi Metode Qo’idah Nuronniyah pada Pembelajaran Tahsin Siswa: Studi Kasus Al-Wildan Islamic School Serpong Tangerang - Rivana, Anggi (IIQ An Nur Yogyakarta, 2025)
Islamic education has a strategic role in shaping the spiritual character of the younger generation, where learning tahsin Al Qur’an is one of the important elements to improve reading according to the rules of tajwid and makhraj. SMP Al-Wildan Islamic School Gading Serpong faces challenges in implementing the Qo'idah Nuronniyah Method, although this method is known to be effective in improving the fluency of reading the Al Qur’an. However, there have not been many studies evaluating the effectiveness of this method at the formal junior high school level, especially in dealing with time constraints and variations in student abilities. Here, the researcher used a qualitative approach with a case study method by integrating interviews, observations, and documentation. The research results showed that this method was successful in improving students' reading fluency, but its effectiveness was influenced by teacher skills and motivation due to limited learning media and low student interest in tahsin learning. The support of digital technology and collaboration with families have been shown to have a positive impact on strengthening learning outcomes. This research emphasizes the importance of developing a more innovative and adaptive approach to improving the quality of learning tahsin Al Qur’an at the secondary school level.